The Influence of the Problem Based Learning (PBL) Learning Model on the Critical Thinking Skills of Grade V - Siagian, Ramces P.; Siagian, Asister Fernando; Sijabat, Desi (CV Putra Publisher, 2026)
This study aims to analyze the influence of the Problem Based Learning (PBL) learning model on the critical thinking skills of fifth-grade students of Sd Negeri 091450 Bah Tongguran. This study was conducted in the fifth grade of Sd Negeri 091450 Bah Tongguran, with the population used being all fifth-grade students of Sd Negeri 091450 Bah Tongguran with a sample of 25 fifth-grade students of Sd Negeri 091450 Bah Tongguran. The results of the study indicate that the use of the Problem Based Learning (PBL) learning model has a positive influence on students' critical thinking skills in the subject of science. This is evidenced by the results of the tests before and after being given treatment (pretest and posttest). Before the application of the Problem Based Learning (PBL) learning model, the average pretest score of students was 49.7143, and after the application of the Problem Based Learning (PBL) learning model it increased to 82.5. From these results, the N-gain value was obtained at 0.63 which is included in the moderate category. In conclusion, students experienced a significant increase in critical thinking skills. This is evidenced by the N-Gain test showing that the N-Gain results of the experimental class obtained an average pretest value of 49.7143 and an average posttest value of 82.5, so that an N-gain of 0.63 was obtained with a moderate category. Based on these data, it can be concluded that there is an Influence of the Problem Based Learning (PBL) Learning Model on the Critical Thinking Skills of Science in Grade V Students of SD Negeri 091450 Bah Tongguran.